Navigating the future of Indian nursing: nurse practitioner in midwifery as an innovation nexus in maternal healthcare - Hemavathi R.; Soumya Krishna Gandavvagol; S. P. Subashini; Gandhimathi R.; S. Tongpangkokla Ozukum; Prathiba S.; Anubha Raina; Aparna Choudhury; Pooja Bakshi; Balamurugan E.; Sowmiya V.; Mohammed Umar (International Journal Of Community Medicine And Public Health, 2026)
The Nurse Practitioner in Midwifery (NPM) programme represents a transformative initiative in India's maternal healthcare system, aiming to strengthen skilled birth attendance, improve the quality of maternity services, and address persistent shortages of qualified maternal healthcare professionals. This narrative review synthesizes current evidence on the evolution, educational framework, clinical roles, policy landscape, implementation challenges, and future prospects of the NPM programme. A comprehensive literature search was conducted across PubMed, Scopus, Web of Science, CINAHL, Embase, Google Scholar, and grey literature from the World Health Organization, International Confederation of Midwives, Indian Nursing Council, and the Ministry of Health and Family Welfare. Evidence indicates that competency-based NPM education aligns with international midwifery standards and prepares nurses to provide autonomous, evidence-based, respectful, and woman-centred maternity care. Midwifery-led continuity models are associated with improved maternal satisfaction, reduced unnecessary obstetric interventions, enhanced breastfeeding practices, and favourable maternal and neonatal outcomes. The review also highlights the growing role of digital health, telehealth, simulation-based education, and artificial intelligence in strengthening advanced midwifery practice. However, implementation remains constrained by regulatory ambiguity, limited professional autonomy, inadequate educational infrastructure, workforce shortages, and uneven adoption of Midwifery-Led Care Units across India. Strengthening legislation, expanding competency-based education, enhancing leadership capacity, and integrating digital innovations are essential for maximizing the impact of NPMs. The Nurse Practitioner in Midwifery programme has substantial potential to advance universal health coverage, improve maternal and newborn health outcomes, and strengthen India's nursing workforce through high-quality, evidence-based maternity care.